The effect of promotion and tuition costs on the determination of higher options - Mohammad Zainul; Ma’rifah Ma’rifah; Syahrial Shaddiq (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
The decision-making process for higher education options is influenced by various factors, including promotions and tuition costs. This study aims to examine and determine whether promotion and tuition fees partially and simultaneously have a significant effect on the choice of college for new students of the 2020/2021 class of the Informatics Management study program, at the State Polytechnic of Banjarmasin. This type of research is explanatory with a quantitative approach. The variables in this study consist of promotion variables, tuition fees variables, and choice selection variables. Sampling using a non-probability sampling technique in which carried out using a convenience sampling technique of 60 respondents with analysis multiple linear. Based on the results of the data analysis carried out, it shows that there is a significant effect of the promotion and tuition fees have an effect on the choice of college for new students.